Reclamation of acid sulphate soils in paddy cultivation area with organic amendments - Muhammad Rendana; Wan Mohd Razi Idris; Sahibin Abdul Rahim; Zulfahmi Ali Rahman; Tukimat Lihan; Habibah Jamil (AIMS Agriculture and Food, 2018)
A soft soil is distinguished by high compressibility and low strength. It is formed in acid sulphate soil under a zero or low pressure gradient as an incompletely consolidated fine grain medium. The problem is related to the presence of weak hardpan structure that permits the soil to experiencing continuous wet condition. The objective of study was to examine closely the effects of addition of organic soil amendment namely Hasil Tani Organic Compound (HTOC) to soft soil in order to enhance its quality and strength. The study was carried out in paddy soils of Muda Agricultural Development Authority (MADA) Alor Senibong Kedah, Malaysia. High water content of soft soil caused low soil strength, which delayed the formation of hardpan layer. The application of HTOC could increase soil strength and reduce water content. After being treated with HTOC, soil strength has increased from 0.22 MPa to 0.70 MPa and organic matter content increased from 3.19% to 7.07%. Whilst, exchangeable sodium percentage (ESP) has decreased from 21% to 5% and soil water content decreased from 40.11% to 24.38%. As whole, the application of HTOC product could improve soft soil in study area.